VIOLENCE, DISCRIMINATION, AND LACK OF LEGAL PROTECTIONS: A COMPARATIVE STUDY OF TRANSGENDER COMMUNITIES IN INDIA AND AMERICA - Rafiq , Anam; Sehrawat, Anil; Singh, Bijendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Transgender communities worldwide face multifaceted challenges, including high rates of violence, systemic discrimination, and inadequate legal protections. This paper explores these issues within two distinct socio-legal contexts: India and the United States. By examining both historical and contemporary factors, it highlights how deeply ingrained biases, institutional failures, and inadequate legal frameworks perpetuate the marginalization of transgender individuals. The paper further compares the evolving legal landscapes in India and America, emphasizing the successes, shortcomings, and areas needing urgent reform. Drawing on existing literature, policy analysis, and grassroots activism, it concludes with recommendations for policymakers, advocacy groups, and researchers to foster a more inclusive and equitable environment for transgender communities in both nations.